2012
DOI: 10.5604/15093492.1005088
|View full text |Cite
|
Sign up to set email alerts
|

Foot and Knee Behaviour During Gait in Response to the Use of Additional Means of Treatment in Celebral Palsied Children

Abstract: Btx-A injections or inhibitive casts improve gait parameters in cerebral palsied children. This improvement is individual and seen in different stages of the support phase, but of similar magnitude following the use of either treatment. Achieving simultaneous improvement in the knee and foot is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A number of studies have demonstrated the benefits of BoNT-A injection for dynamic equinus foot in patients with CP. 1 2 13 14 15 19 34 35 However, previous studies on the effects of such an injection for dynamic equinovarus foot have rarely addressed children with CP. For dynamic equinovarus foot, TP and calf muscles are the target muscles for BoNT-A injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated the benefits of BoNT-A injection for dynamic equinus foot in patients with CP. 1 2 13 14 15 19 34 35 However, previous studies on the effects of such an injection for dynamic equinovarus foot have rarely addressed children with CP. For dynamic equinovarus foot, TP and calf muscles are the target muscles for BoNT-A injection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using computerized gait analysis after BoNT-A injection for equinus foot in children with CP revealed several significant changes in ankle kinematic data and kinetic data. 8 10 11 12 13 14 15 Although used as a gold standard for planning and assessing the outcome of corrective musculoskeletal surgery in CP patients, the computerized gait analysis system has limited ability to reveal significant changes in foot deformities in the frontal plane such as valgus and varus deformities after therapeutic intervention. 16 17 …”
Section: Introductionmentioning
confidence: 99%
“…The current knowledge on the topic demonstrates that the number of muscle synergies is lower in CP than in healthy subjects and it decreases when the GMCSF level increases ( Kim et al, 2021 ). The most affected synergies are those related to the knee-foot and the knee-hip couples, which result to be impaired in most patients ( Thelen et al, 2003 ; Czupryna and Nowotny, 2012 ). In addition, children affected by CP show a higher stride-to-stride variability, which is not observed in healthy controls ( Kim et al, 2018 ; Yu et al, 2019 ; Bekius et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%